Physiotherapy in sport - Piotr Jaworski (Kazimierz Wielki University, 2019)
Both among amateurs and professionals who want to achieve the best possible achievements, sports physiotherapy has a wide field of action. For many years now, the role of physiotherapy in the comprehensive preparation of athletes for a given sport has increased noticeably. Physiotherapy in sport is found, among other things, as a test of predisposition to practice a given discipline, preparation of the body for exercise, health monitoring, post-workout regeneration and injury prevention and treatment. In addition, there are many studies showing the impact of a given sport on the human body.